Development of a mixing device for red mud flocculants. - Dougherty, David J. (Curtin University, 1999)
The performance of flocculants used in the solid-liquid separation of red mud is often compromised by the methods used to mix the fast acting polymers into the slurry. A simple model of the relationship between flocculant performance and intensity of mixing is proposed and a device for mixing flocculant and slurry has been developed on the basis of the model.The intensity of mixing at the point of distributing the flocculant into the slurry is arguably the most important variable influencing the final flocculant performance. This relationship is established using data from flocculation tests in an agitated tank. The flocculant performance is monitored using an optical sensor and the settling rate of the solid-liquid interface is used as a comparison for the optical sensor. The difficulties, errors and merits of the optical sensor to study the flocculation of red mud and automatic control of flocculation processes are also assessed.The mixing device is connected to a pipe for flocculation tests with red mud. For the tests carried out, a high level of flocculation was recorded.The mixing device combines the flocculant and slurry as thin annular jets directed into one another. The opening for the slurry jet can be altered to provide a variation of the mixing that is achieved. The capability of the device to mix rapidly has been assessed using the diazo coupling reactions between l-naphthol and diazotised sulphanilic acid in alkaline, aqueous solution at room temperature. Variables studied included flow rate and slurry jet opening. Better mixing was indicated at higher flow rates and at reduced jet opening. The use of the diazo coupling reactions for studying micromixing is also assessed.